Are Planned Home Births Safe?. Issue 1 (January 2015) - Capitulo', Kathleen Leask; Olafsdottir, Olof Asta; Huang, Zhaoxia
<x xml:space="preserve">Abstract</x> What are the risks to the mother and baby when home birth is planned?